2016 annual competitiveness analysis and development strategies for Indonesia provinces - Tan, Khee Giap; Amri, Mulya; Ahmad, Nursyahida Binte (Asia Competitiveness Institute - World scientific series, 2017)
This book by the Asia Competitiveness Institute (ACI) is an update of ACI's annual study of the competitiveness landscape of 34 Indonesian provinces. With 100 indicators covering four environments and 12 sub-environments of competitiveness, the study's unique methodology incorporates comparative strengths and weaknesses, and 'what-if' policy simulations aimed at policy suggestions for each province. Coupled with evidence-based findings and analyses, this book is a recommended read for policymakers, stakeholders and general audience interested in the economic developments of Indonesia's provinces.